Mixed convection boundary layer of a vicoelastic fluid neara a stagnation point - Nur Ilyana Anwar Apandi, author; Norsarahaida Saidina Amin, author; Sharidan Shafie, author; International Conference on Mathematical Sciences (2007: Skudai) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL